The Effect of Healthcare Workers’ Workload and Competence on Service Quality in Indonesian Hospitals - Vina Anggraini; Suryadi Suryadi; Aida Rachmiana; Muslim Usman (Eastasouth Institute, 2026)
This study examines the effect of workload and healthcare worker competence on service quality in hospitals in Indonesia. A quantitative research design was employed involving 200 healthcare workers selected through purposive sampling. Data were collected using a structured questionnaire measured on a five-point Likert scale and analyzed using SPSS version 25. The analytical procedures included descriptive statistics, validity and reliability tests, classical assumption tests, multiple linear regression, partial t-tests, simultaneous F-tests, and the coefficient of determination. The results indicate that workload has a significant negative effect on hospital service quality. Healthcare worker competence has a significant positive effect on service quality. Simultaneously, workload and competence significantly influence service quality. The coefficient of determination shows that workload and healthcare worker competence explain 44.4% of the variation in hospital service quality, while the remaining 55.6% is explained by other variables outside the model. These findings demonstrate that excessive workload may reduce healthcare workers’ ability to provide timely, accurate, and patient-centered services, whereas higher competence improves professional performance and service delivery. Hospitals should therefore implement balanced workload distribution, adequate staffing, continuous professional training, and competency-based development programs to improve healthcare service quality.